Is it really you, Orthotrichum acuminatum? Ascertaining a new case of intercontinental disjunction in mosses. (January 2016) - Vigalondo, Beatriz; Lara, Francisco; Draper, Isabel; Valcarcel, Virginia; Garilleti, Ricardo; Mazimpaka, Vicente
Abstract : Intercontinental disjunct distributions are a main issue in current biogeography. Bryophytes usually have broad distribution ranges and therefore constitute an interesting subject of study in this context. During recent fieldwork in western North America and eastern Africa, we found new populations of a moss morphologically similar to O rthotrichum acuminatum . So far this species has been considered to be one of the most typical epiphytic mosses of the Mediterranean Basin. The new findings raise some puzzling questions. Do these new populations belong to cryptic species or do they belong to O. acuminatum, a species which then has a multiple‐continent disjunct range? In the latter case, how could such an intercontinental disjunction be explained? To answer these questions, an integrative study involving morphological and molecular approaches was conducted. Morphological results reveal that Californian and Ethiopian samples fall within the variability of those from the Mediterranean Basin. Similarly, phylogenetic analyses confirm the monophyly of these populations, showing that O. acuminatum is one of the few moss species with a distribution comprising the western Nearctic, the western Palaearctic and Palaeotropical eastern Africa. Pending a further genetic and phylogeographical study to support or reject the hypothesis, a process of long‐distance dispersal (LDD) is hypothesized to explain this distribution and the origin of the species is suggested to be the Mediterranean Basin, from where diaspores of the species may have migrated to California and Ethiopia. The spore release process in O. acuminatum is revisited to support the LDD hypothesis, 2015, 180, 30–49.